Professores que atuam na Educação Profissional e Tecnológica: transitando entre a exigência legal e a formativa - DIAS, Ana Paula Mondêgo (2020)
This research is linked to the research group "School, Curriculum and Teacher Training of the Federal University of Maranhão and aims to analyze the demand for pedagogical training for graduate teachers, not graduates, in effective exercise in the teaching profession who work in the technical courses of Technical Professional Education at the Middle Level in the integrated form and its repercussions on pedagogical practice. For this purpose, the theoretical-methodological contribution adopted is that of a critical nature, whose origin and nature of the researched phenomena are revealed without fragmentation of reality. To understand this object, in a process that goes from the known to the unknown and vice-versa, we use in this research "the paradigmatic scheme" of Gamboa, an instrument used for the analysis of scientific production. In this scheme, the research can be organized into different levels (technical, instrumental, methodological, theoretical and epistemological), together with groups of assumptions (gnoseological and epistemological). The development of this research was initially at the methodological level with the analysis of resolutions, decrees, ordinances, legislation and federal constitutions, then at the theoretical level, where it is verified how the TPE is presented in the academic literature and the concepts of teacher training that work in Professional and Technological Education (PTE) based on the following theoretical references: Romanelli (2009), Ferretti (2010), Manfredi (2002), Cunha (2000, 2005), Fonseca (2009), Caires e Oliveira(2016), Kuenzer(2008), Ramos (2011), Ciavatta e Ramos (2011), Oliveira(2006), Gauthier (2013), Gamboa (1998) Gramsci (2010) Tardif (2002, 2014), Gatti (1997), Pena (2014), Saviani (2009), Peréz Gomez (1995), Machado (1998, 2008, 2011), Ghedin (2002), Veiga (2008), Freire(2002) among others. The research is from a qualitative approach, with bibliographic, documental and field analysis. The sample was composed by 11 subjects, being 09 teachers, one pedagogue and the general director of the researched institution, Federal Institute of Education, Science and Technology of Maranhão - Campus Barreirinhas. The data collection was performed through semi-structured interview and participant observation. The results of the survey pointed out the need for the institution in its institutional actions to have a greater follow-up and control over the entry of teachers who work in the institution without pedagogical training. Thus, the training actions should be based on the needs presented by the teachers and thus the graduated teachers, not graduated in effective exercise, in the teaching profession, and already with training, may have relevant contribution to the teaching practice.